Karakteristik Absolut Minyak Atsiri Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Hasil Proses Re-Ekstraksi Concrete Dengan Etanol - Ananta Wibawa, Ida Bagus; Wartini, Ni Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 2 No 2 (2014): September, 2014)
The purposes of this study were 1) to know the effect of re-extraction of essential oils concrete fragrant pandanus leaves with ethanol at various comparison to the rendement and characteristics of the absolute essential oil fragrant pandanus leaves, 2) determine the ratio of concrete with absolute ethanol produces fragrant pandanus leaf essential oil with the highest rendement and the best characteristics, 3) to know the absolute composition of the essential oil fragrant pandanus leaves produced on the best treatment. This research used a randomized block design, concrete comparison with treatment with ethanol, which consists of 7 levels ; 1:2,1:4, 1:6, 1:8, 1:10, 1:12 and 1:14. There are 3 groups based on the time of implementation. The results showed that the re-extraction using ethanol effect on the rendement and characteristics of the absolute essential oil produced fragrant pandan leaves. Re-extraction using ethanol solvent at 1:8 ratio is the best treatment that produces fragrant pandan leaf essential oil, with rendement of 1.11%, the value of preference for the scent of 6.25 (between like really like) and aroma strength of 2.68 (the most powerful) and composed 17 compounds, 8 compounds have identification which consists of: 21,63% alkanes, alkenes 35,39%, 19,59% ketone and 23,38% not identification
Keywords: 22